Analisis Perbedaan Penyerapan Anggaran Program Pembangunan dan Pemberdayaan Kewilayahan di Kota Bandung - muhammad andi septiadi; Siti Alia (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2020)
There are differences in the results of the realization of the PIPPK budget in Cihapit and Merdeka Kelurahan that determine the success of the program in an area. Considering that Cihapit and Merdeka villages are both located in urban areas, but from the results of the 2015 and 2016 budget realization the budget realization in Cihapit Kelurahan can reach 100%, which is one of the best urban villages in the city in the implementation of PIPPK from five other kelurahan. in the city of Bandung. Whereas Merdeka Kelurahan realized its budget was only able to reach 83.19% in 2015 and 84.20% in 2016. With Daniel L. Stufflebeam's theory of Context, Input, Process, and Product Evaluation. The research method in this research is a Descriptive Comparative research method with a qualitative approach, with data collection techniques through library research and field studies. The sampling technique uses non-probability techniques, namely, Purposive Sampling and Snowball Sampling. The results of research and discussion show that the Regional Development and Empowerment Program (PIPPK) in Cihapit Kelurahan can be more successful than Merdeka Kelurahan due to the influence of the Context and Input Evaluations.